PERSEPSI MAHASISWA S1 AKUNTANSI TERHADAP PERUBAHAN STANDAR AKUNTANSI KEUANGAN - Widjaja, Djeni Indrajati; Dermawan, Elizabeth Sugiarto (Akuntansi Krida Wacana, 2018)
This study uses primary data with respondents who represent undergraduate accounting students. The distribution of questionnaires was done either manually or through google form at Tarumanagara University, Universitas Pelita Harapan, Universitas Krida Wacana, and STIE Trisakti. The specific target of this study is to evaluate the academic perspective (undergraduate accounting student) on the change of SAK and the readiness of academics (undergraduate accounting students) to understand the new paradigm contained in SAK. This study also examines the correlation between undergraduate accounting students’ perception on Change of SAK, Expectation of Cost of Benefit, General Interpretation, and Accountability of Accountant’s Responsibility to Perception of Undergraduate Accounting Students on the Benefit of SAK Change. The results of this study indicate that there is a positive and significant influence between the perceptions of undergraduate students of accounting for changes in SAK, on the expectations of cost benefits, and on accountability education responsibilities to the benefits of changes in SAK. On the other hand there is also a positive but insignificant influence from the perception of undergraduate accounting students on the general interpretation of SAK against the benefits of SAK change.Keywords: persepsi, perubahan SAK, harapan biaya manfaat, interpretasi umum, tanggungjawab pendidikan akuntansi, dan keuntungan.